FAKTOR YANG MEMPENGARUHI PERILAKU BERISIKO PADA REMAJA DAERAH TAMBANG - Rahmayanti, Devi; Damayanti, Emmelia Astika F.; Santi, Eka (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2019)
Adolescence is a period of life between childhood and adulthood. During early adolescence,impulsive behavior begins to emerge gradually. Factors that influence risky behavior areendogenous environmental predisposing factors and exodic environmental factors. This studyaims to determine the factors that influence risk behavior in adolescent mining areas. Theresearch was conducted at SDU High School in the Mining Area of Tanah Bumbu Regency,South Kalimantan. This study was an analytic observational study with a cross-sectionalapproach. The sample of this study was 40 teenagers in the Tanah Bumbu mining area.Independent or independent variables of research are environmental factors which include family factors, peer behavior factors, school transition factors, and social denial factors.Dependent or dependent variables are physical signs of risky behavior. The scale used in thequestionnaire is the Likert scale. Spearman correlation test shows there is a relationshipbetween family factors and risk behavior of juvenile mines (sig. 0.02), peer factors indicatethere is a relationship between peer factors and risk behavior of juvenile mines (sig. 0.00),school transition factors indicate there the relationship between school transition factors andrisk behavior of juvenile mines (sig. 0.08), while social denial factors do not indicate arelationship with risky risk management behavior (sig. 0.963). Multivariate analysis usinglogistic regression tests showed that there were three factors related to adolescent behaviorin the mine area namely family, peers and school transitions with P <0.05.